A Prism-Based and Gap-Based Approach to Shopping Location Choice. (December 2014) - Wang, Joshua; Miller, Eric J
In this paper we present a prism-based and gap-based approach to model shopping location choice. Location choice is a fundamental decision in the activity scheduling process. We propose a simple yet robust model to capture shopping location choice behaviour. In this model, an individual first chooses a time window (or gap); the choice of the shopping location depends on the gap chosen. This notion arises from our understanding that shopping location choice behaviour depends on shopping type, scheduling constraints, time of day, and day of week. Or quite simply, where you shop depends on when you shop. The gap-based approach to destination choice is envisioned as a small but significant step towards a more comprehensive location choice model in a dynamic scheduling environment.